Financial Sector and Bilateral Surveillance : Toward Further Integration. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The Fund has continued to make great efforts to enhance financial sector focus and analytics in bilateral surveillance. The main initiatives include enhancing collaboration with other multilateral institutions, improving analytical tools and methodologies, and a major strengthening of the financial sector capabilities in area departments. The fruits of these efforts are already visible in the better treatment of financial sector issues in Article IV reports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet